Axisymmetric vibration analysis of isotropic circular plate with attached annular piezoceramic plate - syed Abu Bakar, Syed Noh; Abdalla, Mostafa M.; Faris, Waleed Fekry; Ihsan, Sany Izan (Inderscience Publishers, 2012)
An axisymmetric vibration analysis of an isotropic circular plate with a piezoceramic annular plate attached to it is presented. The annular plate is attached at the circular plate edge so that the radius of the circular plate is the inner radius of the annular plate. The piezoceramic annular plate is used as the radial in-plane load source. A free vibration analysis of the plates is presented. A parametric study is done to provide some insight into plate geometric influence on fundamental frequency. Lastly, a vibration analysis is done to see the effects of the in-plane loads on the fundamental frequency. The analysis is done by using finite difference method.